Anatomy of the alimentary canal in female Coccoidea: an iconographic review (Bollettino di zoologia agraria e bachicoltura, 2024)
Original observations on the alimentary canal of Coccoidea are reported; they refer to 31 species in the families Ortheziidae, Margarodidae, Pseudococcidae, Eriococcidae, Kermesidae, Micrococcidae, Cerococcidae, Coccidae, Lecanodiaspididae, Aclerdidae, Asterolecaniidae and Diaspididae. Seven types of alimentary canal were found throughout.
Keywords: Coccoidea; alimentary canal; anatomy